THE IMPACT OF USING LOGO PROGRAMMING LANGUAGE ON THE DEVELOPMENT OF SPATIAL VISUALISATION ABILITY AMONG ELEMENTARY SCHOOL STUDENTS - Khormi, Sameer Ali; Alshoshan, Areeb; Binrsheed, Abdulrahman (International Journal of Research -GRANTHAALAYAH, 2021)
This study aims to investigate the effect of using LOGO on the improvement of spatial visualisation abilities among fourth-grade elementary students. In order to achieve this objective, the researchers have selected the Arabic version of spatial ability test prepared by Paul Newton and Helen Bristoll, which involves spatial visualisation perception. The researchers have employed the pre and post-test quasi-experimental approach. The research was applied to a sample group composed of 53 students enrolled in the fourth grade of the elementary stage. The sample group was selected from an elementary school-based in the city of Jeddah, Saudi Arabia. Members of the sample group were randomly and simply divided into two groups; specifically the experimental and control groups. The experimental group was taught using LOGO programming language, while the control group was taught using the traditional method. After implementing the research treatment and processing data and information statistically, findings revealed that there are statistical differences between the two groups; namely, the experimental and control groups – in terms of the development of spatial visualisation perception in favour of the experimental group.